Глава 3.3. Проблеми матеріального та процесуального права на етапі судового розгляду та виконання судових рішень у трудових та сімейних спорах - Мельник, Ярослав Ярославович (Цивільний та виконавчий процес: міжгалузеві зв’язки. Особливості розгляду судами певних категорій справ та виконання судових рішень. Монографія, 2024)
In this section, the specifics of proving negative influence measuresand creating threats of violation of the employee’s labor rights by the employer in the civil process are revealed. In the course of the research, it was found that: (a) a number of actions of the manager or employer regarding the application or creation of the threat of application of negative measuresof influence to the plaintiff (employee) can be legal facts, and have one or more certain conditions/facts related to discrimination; (b) the peculiarity of the duty of proof consists in material-legal and procedural presumptions; (c) the peculiarity of the «standard of proof» is that the concept of limitations in civil procedural law has not yet been developed in the doctrine of civil procedure, and individual publications do not constitute a systematic approach and, therefore, do not solve and describe the problem; the system of evidence based on «threats» has not found proper consolidation in the field of civil procedural legislation, etc.Also, problematic issues of adult adoption are revealed in the research.According to the results of the research, it is proved that in Ukraine during the period of martial law, the courts, considering the case, do not take into account a number of other rights of the adopter and the adult person who wishes to be adopted. In particular, a number of social rights remain neglected. The problem is also the non-differentiated family and social rights between adults and minors; between other subjects of family relations; non-differentiated causes and consequences, grounds for adoption. The participation of the TCC of the JV in the civil process is not sufficiently defined in the CPC of Ukraine.It has been investigated that the court’s review of civil cases on newly discovered circumstances, that the participants who can appeal to the court are not fully defined by law, which poses problems for the protection of human rights.Within the framework of the part of the study on the execution of court decisions, the author proves the need to change the law in terms of loosening the regime of execution of court decisions regarding cases that are subject to immediate execution (collection of alimony, reinstatement).